Pacific economic monitor July 2017. (Metro Manila, Philippines Asian Development Bank, 2017)
To help overcome remoteness, Pacific economies are looking to improve economic integration not only through ICT and transport network investments, but also by promoting greater competition and private investment.
Keywords: Economic integration -- Developing countries; Economic policy -- Developing countries; Electronic books